The stone huntsman spider genus Eusparassus (Araneae: Sparassidae): systematics and zoogeography with revision of the African and Arabian species - Moradmand, Majid (Zootaxa, 2013)
An overview on the systematics of the stone huntsman spider genus Eusparassus Simon, 1903 and an identification key to the known species are presented. Six species-groups are proposed: the walckenaeri group (3 species, Eastern Mediter-ranean to Arabia and parts of North-Eastern Africa), dufouri group (8 species, Iberian Peninsula to parts of North-western Africa), vestigator group (3 species, Central to Eastern Africa and an isolated area in India), jaegeri group (4 species, Southern and South-Eastern Africa), tuckeri group (2 species, South-Western Africa) and doriae group (7 species, Middle East to Central and South Asia). Two species, E. pontii Caporiacco, 1935 and E. xerxes (Pocock, 1901) could not be placed MORADMAND 4 · Zootaxa 3675 (1) © 2013 Magnolia Press in any of the above groups. The species from Africa and Arabia are revised. The following ten species are re-described: Eusparassus barbarus (Lucas, 1846), E. atlanticus Simon, 1909 stat. nov., E. syrticus Simon, 1909, E. oraniensis (Lucas, 1846), E. letourneuxi (Simon, 1874), E. fritschi (Koch, 1873) stat. rev., E. walckenaeri (Audouin, 1826), E. vestigator (Simon, 1897) comb. nov., E. laevatus (Simon, 1897) comb. nov. and E. tuckeri (Lawrence, 1927) comb. nov. The latter three species are transferred from Olios Walckenaer, 1837. Seven new species are described: Eusparassus arabicus spec. nov. (male, female) from Arabian Peninsula, E. educatus spec. nov. (male, female) from Namibia, E. reverentia spec. nov. (male, female) from Burkina Faso and Nigeria, E. jaegeri spec. nov. (male, female) from South Africa and Botswana, E. jocquei spec. nov. (male, female) from Zimbabwe, E. borakalalo spec. nov. (female) from South Africa and E. schoem-anae spec. nov. (male, female) from South Africa and Namibia. Three taxa, E. dufouri maximus Strand, 1906 syn. nov., E. rufobrunneus Caporiacco, 1941 syn. nov. and Olios furcatus Lawrence, 1927 syn. nov. are proposed as junior syn-onyms of E. oraniensis, E. vestigator comb. nov. and E. tuckeri comb. nov. respectively. Males of E. atlanticus stat. nov. and E. fritschi stat. rev. are described for the first time as in the female of E. vestigator comb. nov. Neotypes are desig-nated for E. barbarus, E. oraniensis and E. letourneuxi (all from Algeria). The male and female of Cercetius perezi Simon, 1902, which was known only from the immature holotype, are described here for the first time. This resulted in recogniz-ing the monotypic and little used generic name Cercetius Simon, 1902 as a synonym of the widely used name Eusparas-sus. Nearly all the species are illustrated for the first time. Eusparassus concolor Caporiacco, 1939 is transferred to Olios and the replacement name Olios quesitio is proposed because of secondary homonymy. For the majority of the species, new geographical records are presented. The systematics and zoogeography of the currently known species and species groups are discussed. A brief note on the copulation process of E. walckenaeri is presented.